FAKTOR-FAKTOR YANG MEMPENGARUHI BOOK TAX GAP DAN PENGARUHNYA TERHADAP PERSISTENSI LABA - Sawiji Wihardiningrum; Titik Aryanti (Jurnal Magister Akuntansi Trisakti, 2015)
The aim of this study is to examine the factors affecting book tax gap and the persistence of earnings. Factors which are predicted affect the book tax gap are fixed asset and intangible assets, revenue movements, tax loss carried forward balance and size of the company. Meanwhile variables in which affect earning persistance are the component of temporary book tax gap and permanent book tax gap and the control variable such as Return on Asset movement (ΔROA), size of the company, operating cash flow dan accrual.The result suggests that, fixed asset and intangible assets and the size of the company affect the book tax gap, meanwhile tax loss carried forward and revenue growth are not affecting the book tax gap. Book tax gap component variable, return on assets movement, the size of the company, operating cash flows and accruals affect the persistence of earning. Referring to the book tax gap component test, variabel book tax gap such as amortisation, allowance for inventory obsolence, allowance for post service liability, subidiary’s income, and income which are not subject to Income Tax are not affecting the persistence of earning.